The complete chloroplast genome sequence of the Nymphaea capensis Thunb. (Nymphaeaceae) - Yongsung Kim; Juhyeon Min; Woochan Kwon; Myeoung Joon Song; Suhwan Nam; Jongsun Park (Mitochondrial DNA. Part B. Resources, 2019)
Nymphaea capensis (Nymphaeaceae) is one of the species in subgenus Brachyceras, which usually found in tropical and subtropical areas. Here, we presented a complete chloroplast genome of Nymphaea capensis which is 159,998 bp long and has four subregions: 90,134 bp of large single copy (LSC) and 19,504 bp of small single copy (SSC) regions are separated by 25,180 bp of inverted repeat (IR) regions including 130 genes (85 protein-coding genes, eight rRNAs, and 37 tRNAs). The overall GC content of the chloroplast genome is 39.2% and those in the LSC, SSC, and IR regions are 37.8%, 34.5%, and 43.4%, respectively. Phylogenetic tree constructed with the whole chloroplast genomes present phylogenetic position of subgenus Brachyceras with available Nymphaea chloroplast genomes.